A regenerable screen-printed DNA biosensor based on acrylic microsphere-gold nanoparticle composite for genetically modified soybean determination - Ulianas A.; Heng L.Y.; Ahmad M.; Lau H.-Y.; Ishak Z.; Ling T.L. (2024)
Indexed by WOS/Scopus